Pengaruh Relationship Marketing Terhadap Loyalitas Pelanggan (Studi Pada PT. Pegadaian (Persero) jalan Basuki Rahmat No.2 Samarinda, Kalimantan Timur) - Fachrozi Sukma Wardana (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The concept of Relationship Marketing is a business model with the main purpose of identifying, anticipating , understanding customer needs , as well as parties with potential customers by collecting information about customers , sales , marketing effectiveness , and market trends . This study aims to determine the effect Relationship Marketing is comprised of Finansial Bonds, Social Bonds, Structural Bonds to Customer Loyalty in PT . Pegadaian ( Persero ) Basuki Rahmat road , Samarinda , East Kalimantan. Sample of 100 respondents drawn using sampling techniques and sampling nonprobability field using accidental sampling technique . The analysis used is multiple regression analysis. Based on t test , the results obtained that Finansial Bonds, Social Bonds, Structural Bonds positive and significant impact on customer loyalty . In this study, obtained the coefficient of determination ( R2 ) of 0.492 means that the model coefficient of determination nice . This shows that 49.20 % customer loyalty in PT . Pegadaian ( Persero ) is influenced by a variation of the three independent variables : Finansial Bonds, Social Bonds, Structural Bonds. While the remaining 50.80 % influenced by other variables that are not in thoroughly